Skill Gap Analysis in Silkworm Rearing among Farmers and Extension Workers in Eastern India - Shafi Afroz, Manjunatha GR, T.D. Biswas; D. Pandit (Indian Journal of Extension Education, 2018)
Skills are ingredients of productivity and profitability for any of the undertaking. Attaining appropriate technical skills triggers development as well as innovation. This paper engrossed on the skill gaps and training needs of farmers and extension workers in silkworm rearing of Eastern India. Data was collected from 300 randomly selected mulberry sericulture farmers from 4 districts of West Bengal (2), Bihar (1) & Jharkhand (1) and 50 extension workers of the study area. Forty-five skills items were used as a checklist for measuring silkworm rearing skill competency levels using the Likert rating scale. Descriptive statistics and exploratory Principal Component Analysis (Orthogonal rotation technique) was performed on the collected data. Findings revealed that, farmers showed competencies in seven skill items only out of 45 skill items which included appropriate discarding of diseased worms (x = 3.68); identification of moulting (x = 3.55) and ability to identify matured worms (x = 3.96), amongst others; while the extension workers showed competency in 31 skills items. Nine factors with Eigen value of >1, accounted for 61.824% were extracted, with each factor loading ranging from 0.362 to 0.937. Factor loading after rotation were described as disinfection and hygiene of rearing house; disease management in late age rearing; incubation of silkworm eggs; environment conditions and hygiene during young age, late age and mounting of silkworms; disinfection; hygiene; mounting, harvesting and record keeping and marketing. It is recommended that intensive training is needed for both the farmers and the extension workers for up scaling skills and practices in the sericulture